Association of thrombophilia and catheter‐associated thrombosis in children: a systematic review and meta‐analysis. (29th July 2016) - Neshat‐Vahid, S.; Pierce, R.; Hersey, D.; Raffini, L. J.; Faustino, E. V. S.
Abstract : Essentials It is unclear if thrombophilia increases the risk of catheter‐associated thrombosis in children. We conducted a meta‐analysis on thrombophilia and pediatric catheter‐associated thrombosis. Presence of ≥1 trait confers additional risk of venous thrombosis in children with catheters. Limitations of included studies preclude us from recommending routine thrombophilia testing. Summary: Background: The association between thrombophilia and deep vein thrombosis (DVT) associated with central venous catheter (CVC) use, the most important pediatric risk factor for thrombosis, is unclear in children. Pediatric studies with small sample sizes have reported conflicting results. We sought to evaluate whether, among children with CVCs, thrombophilia increases the risk of CVC‐associated DVT (CADVT). Materials and methods: We systematically searched MEDLINE, EMBASE, the Web of Science, the Cochrane Central Register for Controlled Trials, PubMed and reference lists for controlled studies published from the inception of the database until September 2015. Included were studies of children aged <21 years with CVCs who were systematically tested for thrombophilic traits that are commonly screened for in clinical practice. Pooled prevalence rates and pooled odds ratios (pORs) of CADVT with thrombophilia were estimated by use of a random effects model. Results: We analyzed 16 cohort studies with 1279 children, 277 of whom had CADVT, and with 12 traits tested. There was significant heterogeneity in the included studies. The presence of one or more traits was associated with CADVT (pOR 3.20; 95% confidence interval [CI] 1.56–6.54). Although the prevalence of most traits was < 0.10, children with protein C deficiency, elevated factor VIII levels and the FV Leiden mutation had an increased prevalence of CADVT. The association with thrombophilia seemed to be stronger for symptomatic CADVT (pOR 6.71; 95% CI 1.93–23.37) than for asymptomatic CADVT (pOR 2.14; 95% CI 1.10–4.18). Conclusions: On the basis of the low prevalence of specific traits, the relatively weak association with CADVT, and the limitations of the included studies, we cannot recommend routine testing of thrombophilias in children with CADVT.